(untitled) (Research, Society and Development, 2020)
The aim to evaluate whether different beak trimming methods affected the performance and well-being of laying hens raised in cage and floor systems. During the starter phase, we used a completely randomized design, with three treatments (hot blade beak trimming, infrared beak trimming, and no beak trimming (control)), with four repetitions and in the grower and production phase, we used a factorial arrangement scheme involving two production systems (cage or floor) and three beak management methods (as above). We reared the birds in starter, grower and production phases over a course of 30 weeks. We evaluated productivity, egg quality, behavioral parameters and biochemical variables. In the starter phase, control birds showed higher blood glucose levels (p=0.043). In the grower phase, birds subjected to hot blade beak trimming and control birds showed lower feed intake and better feed conversion. Triglyceride levels were higher in the cage rearing system (p<0.05). In the production phase, the cage rearing system showed higher productivity (p<0.05), mean egg weight (p<0.01), cholesterol levels (p<0.05) and oxygen reactive species levels (p<0.05). In the production phase, the floor system gave rise to a higher frequency of comfort movement behaviors (p<0.01). Hens in cage had improved their performance and had greater egg production efficiency. The choice of the beak method depends on the breeding system.